Oxford basic English dictionary (Oxford University Press, 2012)
Oxford Basic Dictionary gives all the essential help and information elementary and pre-intermediate learners need. It includes over 19,200 words, phrases and meanings and identifies the 2,000 most important words in English so students know which words to learn first.